2013
DOI: 10.1098/rsif.2012.0920
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetically and oceanographically distinct blooms of jellyfish

Abstract: Reports of nuisance jellyfish blooms have increased worldwide during the last half-century, but the possible causes remain unclear. A persistent difficulty lies in identifying whether blooms occur owing to local or regional processes. This issue can be resolved, in part, by establishing the geographical scales of connectivity among locations, which may be addressed using genetic analyses and oceanographic modelling. We used landscape genetics and Lagrangian modelling of oceanographic dispersal to explore patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 77 publications
(113 reference statements)
1
44
1
Order By: Relevance
“…Moreover, the basal phylogenetic position of the main phyla Cnidaria and Ctenophora (Giribet et al 2007, Hejnol et al 2009) has spurred considerable scientific interest in the fields of evolutionary and developmental research (Pang & Martindale 2008a, Lange et al 2010. However, the presence of, and underlying causes for, population structure, gene flow and population turnover in jellyfish are currently not well understood, but are of growing interest (Licandro et al 2010, Stopar et al 2010, Lee et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the basal phylogenetic position of the main phyla Cnidaria and Ctenophora (Giribet et al 2007, Hejnol et al 2009) has spurred considerable scientific interest in the fields of evolutionary and developmental research (Pang & Martindale 2008a, Lange et al 2010. However, the presence of, and underlying causes for, population structure, gene flow and population turnover in jellyfish are currently not well understood, but are of growing interest (Licandro et al 2010, Stopar et al 2010, Lee et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The perceived increased frequency of blooms of jellyfish in the world's ocean (Mills 2001;Purcell et al 2007;Purcell 2012;Condon et al 2012Condon et al , 2013Lee et al 2013) has intensified research efforts to understand the population dynamics of gelatinous plankton, with the majority of research having been conducted on the conspiculous medusoid life stages . Medusae in the genus Aurelia Lamarck, 1816 have been reported to occur in the world's oceans from 70° N to 40° S where they are most commonly found along continental shelves or close to large islands (Mayer 1910;Kramp 1961;Russell 1970;Miyake et al 2002;Schroth et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In general, holopelagic scyphozoans with high dispersal potential showed genetic homogeny over large geographical distances (Stopar et al, 2010). In contrast, the increased genetic diversity observed for meroplanktonic scyphozoans may be closely linked to the benthic phase (Gibbons et al, 2010;Lee et al, 2013). For example, the holopelagic scyphozoan Pelagia noctiluca showed a lack of genetic structure among Mediterranean and East Atlantic populations (Stopar et al, 2010), while significant genetic structures distinguishing three populations in the meroplanktonic scyphozoan jellyfish Rhizostoma octopus were revealed in the Irish Sea and northeastern Atlantic (Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…These results suggested that Aurelia sp.1 might have dispersed globally from Japanese coastal waters. A few studies have addressed the population genetic structure in scyphozoans, suggesting that both different reproductive strategies and dispersal ability may attribute to the population genetic structure (Stopar et al, 2010;Ram sak et al, 2012;Lee et al, 2013). In general, holopelagic scyphozoans with high dispersal potential showed genetic homogeny over large geographical distances (Stopar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%